2022
DOI: 10.1093/cei/uxac022
|View full text |Cite
|
Sign up to set email alerts
|

Profile of circulating extracellular vesicles microRNA correlates with the disease activity in granulomatosis with polyangiitis

Abstract: Granulomatosis with polyangiitis is a chronic systemic inflammation of small vessels characterized by circulating anti-proteinase 3 antibodies. MicroRNA are short transcripts specifically inhibiting protein translation. Neutrophils can release extracellular vesicles. In this study we characterised profile of microRNA trafficked by extracellular vesicles in GPA. Fifty patients with GPA were enrolled in the study, 25 at acute phase and 25 in remission. Extracellular vesicles were isolated from the blood serum, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Marcin et al. reported that miR-664a-3p was overexpressed in GPA and could discriminate between active disease and remission [20] . MiR-644a was decreased in blood and tissue samples from Lichen sclerosis (LS) patients compared with that in samples from healthy female volunteers [46] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marcin et al. reported that miR-664a-3p was overexpressed in GPA and could discriminate between active disease and remission [20] . MiR-644a was decreased in blood and tissue samples from Lichen sclerosis (LS) patients compared with that in samples from healthy female volunteers [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports have shown that miR-664a-3p, which is genomically located in the intron of RAB3 GTPase Activating Non-Catalytic Protein Subunit 2 (RAB3GAP2), is abnormally expressed in a number of cancers, including gastric cancer, cervical cancer, osteosarcoma, breast cancer, and T-cell acute lymphoblastic leukaemia [15] , [16] , [17] , [18] , [19] . Another study demonstrated that there were increased levels of miR-664a-3p in EVs in granulomatosis with polyangiitis (GPA), which could be used to discriminate between active GPA and remission [20] . However, it is unclear whether miR-664a-3p expression is altered in pancreatic cancer tissues or plasma sEV.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of miR-30a-5p, miR-99a-5p, miR-106b-5p and miR-182-5p in urinary EVs were identified as novel biomarkers of antineutrophilic cytoplasmic antibody (ANCA)-associated vasculitis [153]. Expression of miR-223-3p in circulating EVs discriminates between granulomatosis with polyangiitis (GPA) patients and healthy controls, whereas miR-664-3p was identified as a novel biomarker for disease activity [154]. Expression levels of miR-146a-5p were particularly high in histologically positive temporal artery biopsies of giant cell arteritis (GCA) patients, while levels of miR-424-5p were associated with vision disturbances [149].…”
Section: Autoimmune Vasculitismentioning
confidence: 99%